Noninvasive Brain Stimulation Therapies to Promote Recovery of Consciousness: Where We Are and Where We Should Go - Barra, Alice; Monti, Martin; Thibaut, Aurore (Seminars in Neurology, 2022)
Therapeutic options for patients with disorders of consciousness (DoC) are still underexplored. Noninvasive brain stimulation (NIBS) techniques modulate neural activity of targeted brain areas and hold promise for the treatment of patients with DoC. In this review, we provide a summary of published research using NIBS as therapeutic intervention for DoC patients, with a focus on (but not limited to) randomized controlled trials (RCT). We aim to identify current challenges and knowledge gaps specific to NIBS research in DoC. Furthermore, we propose possible solutions and perspectives for this field. Thus far, the most studied technique remains transcranial electrical stimulation; however, its effect remains moderate. The identified key points that NIBS researchers should focus on in future studies are (1) the lack of large-scale RCTs; (2) the importance of identifying the endotypes of responders; and (3) the optimization of stimulation parameters to maximize the benefits of NIBS.
Keywords: neuromodulation; brain injury; coma; vegetative state; minimally conscious state; tDCS; transcranial magnetic stimulation; traumatic brain injury